ROOT CAUSE ANALYSIS OF NON PERFORMING FINANCING ON MURABAHAH FINANCING (STUDY OF COSTUMER AT BPRS ADECO KOTA LANGSA DURING COVID-19 PANDEMIC) - Tajul, Tajul Ula; Safwan Kamal; Khairul Fuady; Annisa Ul Husna ZF (IHTIYATH : Jurnal Manajemen Keuangan Syariah, 2022)
This study aims to examine root cause analysis on murÄbaá¸¥ah financing at BPRS Adeco Langsa City during covid-19. This study uses a qualitative descriptive research method. The main data used in this research is primary data by conducting interviews with the Director and Account Officer (AO) and customers of BPRS Adeco Langsa city. The results of this study reveal that the COVID-19 pandemic has had a major impact on various sectors, especially banking, which caused problems in non-performing financing. This study uses root cause analysis using the 5 why analysis method. The results of the analysis in this study find several root causes which were concluded based on information provided by research informants which exhibit that non-performing murabahah financing of the customers at the bank is basically because of economic conditions in the midst of this pandemic which forced customers to delay their obligation to pay their installment. There are 3 main factors or root causes of customers that cause non-performing murabahah financing of the customers at the bank as follows a decrease in income, huge cost of educationalneedss, and the abundance of household needs to prioritize.